Diagnostic rigid and flexible oesophagoscopy in carcinoma of the oesophagus: a comparison. - Ritchie, A J (1993)
BACKGROUND: Flexible oesophagoscopy is regarded as superior to rigid oesophagoscopy on the basis of perforation rates as an end point. This advantage may be more apparent than real because no comparison has been made in a diagnostic setting in patients with carcinoma of the oesophagus with both perforation rate and diagnostic efficacy as indices. METHODS: A retrospective analysis was carried out on data on 336 diagnostic oesophagoscopies in patients with carcinoma of the oesophagus, comparing rigid with flexible oesophagoscopy. RESULTS: Both rigid and flexible oesophagoscopies were performed without perforation when they were used for diagnosis only. Rigid biopsy achieved a diagnostic success rate of 99.3%, compared with 80.5% for flexible oesophagoscopy. CONCLUSIONS: Diagnostic oesophagoscopy can be achieved without perforation with either instrument, but the chance of diagnosing carcinoma was significantly greater with the rigid instrument.